(untitled) (Web of Teachers: Inderscience Research, 2024)
Up until recently, one big problem with online courses was that it was very difficult to do speaking activities. With no audio or video live element, online language courses of as little as five or ten years ago were much more heavily weighted towards writing or discrete item testing of grammar and vocabulary. With the arrival of better and more stable video conferencing tools and (perhaps more importantly) the growing availability of internet access that can handle video and audio it is now possible to begin contemplating real-time speaking activities. The widespread use of audio and video recording software and better cameras on mobile devices also afford our learners chances to ‘do’ speaking asynchronously.